ANALISIS KINERJA PEGAWAI DALAM PENYELENGARAAN PELAYANAN PUBLIK DI SEKRETARIAT DPRD KOTA SUNGAI PENUH: EKA SEPTIANI, S.Sos., M.Si - Eka Septiani (LPPM STIA Nusantara Sakti, 2018)
Method Research weared by is quantitative descriptive method. Election all Responder In this Research come from Receiver of Service which in finding at Secretariat of DPRD Full of Town River. Instrument Research is researcher alone and data collecting through kuisioner, field observation and interview. Technique analyse data in this research use Scale analyzer of likers. Make-Up of Performance Officer in management Service of Public in Secretariat of DPRD this Full of Town River include, cover the Quality of Job, Amount, Mainstay. Attitude Officer of is Make-Up of Performance Officer in management Service of Public in Secretariat of DPRD Full Of Town River. Condition of Performance Officer in management Service of Public in Secretariat of DPRD Full of Town River which felt by still less precise. Make-Up of Performance Officer in management Service of Public in Secretariat of DPRD Full of Town River reside in at international 61,05 % with the meaning Make-Up of Performance Officer in management Service of Public in Secretariat of DPRD Full of Town River in categorize Whether, Suggestion able to be told in skripsi is the Make-Up of Performance Officer in management Service of Public in Secretariat of DPRD Full of Town River to in revising and in improving again